Self-Regulation, Engagement, and Developmental Functioning in Preschool-Aged Children - Coelho, Vera (2018)
Self-regulation can be relevant for engagement, as children need to be able to modulate behaviors and control attention to be engaged. Although previous studies focus on the relation between self-regulation and engagement, little is known about this subject in children with disabilities or at risk. This study analyzes relations between self-regulation and engagement in inclusive preschool settings, considering children’s developmental functioning (DF). The main goal is to examine whether DF moderates the relation between self-regulation and engagement. Participants include three groups of children: with disabilities (n = 54), at risk (n = 78), and typically developing (n = 115). DF was assessed with a short version of the Matrix for Assessment of Activities and Participation; self-regulation with Head-Toes-Knees-Shoulders; and engagement with Child Observation in Preschool. Results indicated that higher levels of self-regulation were related to higher levels of engagement. A moderation effect between self-regulation and DF was also found: in the group of children with disabilities, the influence of self-regulation on engagement was larger. This highlights the relevance of promoting self-regulation, particularly in children with lower DF.